A multiplicity theorem for Fréchet spaces - Eftekharinasab, K.A. (Reports of the National Academy of Sciences of Ukraine, 2022)
This note serves to announce a multiplicity result for Keller C1c -functionals on Fréchet spaces which are invariant under the action of a discrete subgroup. For such functionals, we evaluate the minimal number of critical points by applying the Lyusternik—Schnirelmann category.